ANALISIS SWOT DALAM UPAYA PENGEMBANGAN BISNIS MEUBEL DI BM. SUKA PIRING MEDAN - Dwi Fajar Rastiti (Jurnal Niaga & Bisnis (e-journal), 2014)
The purposeofthis studywas to determine the environmental condition of the internal and external environment BM furniture business. Dishes like and to determine the right strategy in BM furniture business development efforts. Dishes like to be able to survive and compete with other similar businesses. And determine the business strategy of the company diterpakan based SWOT analysis diagram, IFAS, EFAS. Form of research used in this study was descriptive eusing qualitative data analysis. Methods of data collectionby observation, interview, kand Tudi documentation. Analysis using matrix method IFAS and EFAS, IFAS+EFAS matrix incorporation, quadrant SWOT and SWOT matrix. The results show that the current internal capabilities BM furniture business. Dishes like in adequate for a large market opportunity, so in need of holding the increase in the internal environment in order to survive. Based on the analysist hatapplied the right strategy is an aggressive strategy or growth strategy, which can increase sales volume and expand market share by increasing its weakness esto deal with a large market share. Keywords: SWOTAnalysis, Business Development, FurnitureStore